Atom Probe Tomography Study of As‐Quenched Al–Mg–Si Alloys1 . Issue 4 (23rd December 2016) - Dumitraschkewitz, Phillip; Gerstl, Stephan S. A.; Uggowitzer, Peter J.; Löffler, Jörg F.; Pogatscher, Stefan
Abstract : This study deploys a new method to gain insight into the as‐quenched microstructure of Al–Mg–Si alloys using atom probe tomography (APT) as an imaging method. Here, diffusion of solutes during sample preparation and handling is suppressed via application of cryogenic temperatures beginning from quenching in liquid nitrogen (LN2) through to APT experiments at 33 K. The solute distribution is studied via customized nearest‐neighbor distribution and radial distribution function analysis. The influence of energy input on the solute distribution via cryogenic focused ion beam (FIB) preparation is also shown. Abstract : In this study a new method is deployed to gain insight into the as‐quenched microstructure of Al–Mg–Si alloys using atom probe tomography. The diffusion of solutes during sample preparation and handling is suppressed via application of cryogenic temperatures, starting from quenching in liquid nitrogen through to APT experiments at 33 K. The solute distribution is studied.